2019
DOI: 10.1039/c8ra10071c
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of halogen-free flame retardant and phosphorus-containing aromatic poly(1,3,4-oxadiazole)s fiber

Abstract: The flame resistance of POD fibers can be improved significantly by introducing TPO units into the main chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Researchers studied an additional class of high-performance polymer, polyoxadiazoles, to enhance material flame retardancy via phosphorus-containing and non-phosphorus-containing methods. Liu et al 146 reported novel polyoxadiazoles that contain triphenylphosphine oxide units. Figure 22(a) shows the synthetic pathway.…”
Section: Polyesters/copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers studied an additional class of high-performance polymer, polyoxadiazoles, to enhance material flame retardancy via phosphorus-containing and non-phosphorus-containing methods. Liu et al 146 reported novel polyoxadiazoles that contain triphenylphosphine oxide units. Figure 22(a) shows the synthetic pathway.…”
Section: Polyesters/copolymersmentioning
confidence: 99%
“…(a) Synthetic route to phosphine‐oxide‐containing poly(oxadiazole)s. (b) LOI and gross heat of combustion (GHC) as a function of bis(4‐carboxyphenyl)phenyl phosphine oxide content for the poly(oxadiazole)s. Adapted from Liu et al 146 . with permission from the Royal Society of Chemistry.…”
Section: Polymeric Compositionsmentioning
confidence: 99%
“…In addition to the common five membered ring azaheterocycles mentioned above, oxadiazoles and their derivatives, thiazoles and their derivatives, , tetrazoles and their derivatives, etc., have also been investigated as flame retardants. Xu et al prepared halogen-free flame-retardant POD fibers by incorporating triaryl phosphine oxide (TPO) units into the main chains of aromatic polyoxadiazole (p-POD). The results showed that the introduction of TPO units significantly improved the flame retardancy of POD fibers, which was attributed to the TPO units’ ability to inhibit the generation of volatile products and enhance the flame-retardant effect of the condensed phase.…”
Section: Application Of Flame-retardant Molecules Featuring the Azahe...mentioning
confidence: 99%
“…In the pursuit of developing advanced materials, researchers have turned their attention to enhancing the flame-retardant properties of poly(1,3,4-oxadiazole-esterimide)s by incorporating phosphorus-containing moieties into their structures. 18,19 Phosphorus-based flame retardants have shown promise in mitigating fire hazards, especially in environments where stringent fire safety standards are essential. 20 Moreover, these compounds offer environmentally friendly alternatives, minimizing the production of toxic byproducts during combustion.…”
Section: Introductionmentioning
confidence: 99%